2019
DOI: 10.1093/nar/gkz702
|View full text |Cite
|
Sign up to set email alerts
|

TrmB, a tRNA m7G46 methyltransferase, plays a role in hydrogen peroxide resistance and positively modulates the translation of katA and katB mRNAs in Pseudomonas aeruginosa

Abstract: Cellular response to oxidative stress is a crucial mechanism that promotes the survival of Pseudomonas aeruginosa during infection. However, the translational regulation of oxidative stress response remains largely unknown. Here, we reveal a tRNA modification-mediated translational response to H2O2 in P. aeruginosa. We demonstrated that the P. aeruginosa trmB gene encodes a tRNA guanine (46)-N7-methyltransferase that catalyzes the formation of m7G46 in the tRNA variable loop. Twenty-three tRNA substrates of Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 49 publications
4
45
0
Order By: Relevance
“…The most common exogenous and endogenous stressors are reactive oxygen species (ROS). It has been shown that some tRNA modifications (e.g., methylation and thiolation) can modulate oxidative stress response in bacteria [ 8 , 9 , 86 ]. Adding ROS scavenging agents to the growth medium of bacteria could indicate whether the elevated mutation frequency originates from reduced tolerance to intracellular ROS levels [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common exogenous and endogenous stressors are reactive oxygen species (ROS). It has been shown that some tRNA modifications (e.g., methylation and thiolation) can modulate oxidative stress response in bacteria [ 8 , 9 , 86 ]. Adding ROS scavenging agents to the growth medium of bacteria could indicate whether the elevated mutation frequency originates from reduced tolerance to intracellular ROS levels [ 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in yeast there are Ψ38 or Ψ39 in at least 19 tRNAs, but the temperature-sensitive phenotype of the Pus3p mutant is mainly due to a defect in tRNA gln(UUG) , showing that Ψs can have distinct effects on different tRNAs [ 101 ]. In addition, although in P. aeruginosa TrmB methylates many tRNAs, the expression of KatA and KatB is selectively upregulated at the translation level, since both, katA and katB gene, are enriched in Phe and Asp codons [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, m 7 G46 catalyzed by tRNA guanine-N7-methyltransferase (trmB) is important for decoding efficiency of tRNA Asp GUC and tRNA Phe GAA . In P. aeruginosa, loss of trmB has a strong negative effect on the translation of Phe-and Asp-enriched mRNAs, including those coding the major peroxide detoxifying enzymes, the catalases KatA and KatB, resulting in oxidative stress-sensitive phenotype [173]. Using tRNAseq and mass spectrometry performed on Vibrio cholera revealed specific modifications in various tRNAs that were not described in E. coli tRNAs [174].…”
Section: Trna Modificationsmentioning
confidence: 99%
“…In Escherichia coli and other bacteria, the hypomodification of tRNAs can result in decreased growth rates, altered metabolic requirements, and reduced stress resistance [5][6][7][8]. Loss of tRNA modifications can also impact the fitness and virulence potential of many important bacterial pathogens, including Streptomyces pyogenes, Pseudomonas spp., Shigella flexneri, Agrobacterium tumefaciens, Mycobacterium tuberculosis, Aeromonas hydrophila, Streptococcus spp., and Salmonella enterica serotype Typhimurium [6,[9][10][11][12][13][14][15][16][17][18][19][20][21]. Together, these findings suggest that tRNA modification serves as a regulatory nexus that can control a wide array of bacterial activities.…”
Section: Introductionmentioning
confidence: 99%